Hyaluronic acid coating of gold nanoparticles for intraocular drug delivery: Evaluation of the surface properties and effect on their distribution. (September 2020) - Apaolaza, P.S.; Busch, M.; Asin-Prieto, E.; Peynshaert, K.; Rathod, R.; Remaut, K.; Dünker, N.; Göpferich, A.
Abstract: Due to the unique anatomical structure of the eye, ocular drug delivery is a promising delivery route for the treatment of several ocular diseases, such as the ocular neovascularization that contributes to diabetic retinopathy. This disease is triggered by inflammation, retinal ischemia, and/or deposits of advanced-glycation end-products (AGEs), as well as increased levels of vascular endothelial growth factor (VEGF), interleukins, or reactive oxygen species (ROS). Gold has unique antioxidant and antiangiogenic properties and can inhibit angiogenic molecules. Furthermore, gold nanoparticles (GNPs) are not only biocompatible, they are easy to synthesize, they absorb and scatter visible light, and they can be made with precise control over size and shape. GNPs are an excellent candidate for ocular drug delivery because they can be conjugated to an extraordinarily diverse array of different biomolecules, and surface functionalization can improve the mobility of GNPs across the physiological barriers of the eye, such as the vitreous humour or the inner limiting membrane. For this purpose, we employed low molecular weight hyaluronan (HA) to increase the mobility of the nanoparticles as well as target them to HA receptors that are expressed in different cells of the eye. In this study, the combination of gold and HA enhanced the stability of the whole carrier and promoted their distribution across ocular tissues and barriers to reach the retina. Moreover, analysis in vitro, ex vivo, and in ovo revealed the protective and antiangiogenic effect of GNPs as inhibitors of AGEs-mediated- retinal pigment epithelial cell death and neovascularization. We demonstrated that conjugation with HA enhances GNP stability and distribution due to a specific CD44 receptor interaction. The capacity of HA-GNPs to distribute through the vitreous humour and their avidity for the deeper retinal layers ex vivo, suggest that HA-GNPs are a promising delivery system for the treatment of ocular neovascularization and related disorders. Highlights: Surface functionalization improves the pass of gold nanoparticles across eye barriers. Hyaluronan enhances the biodistribution of gold nanoparticles through the retina. Gold nanoparticles show protective and antiangiogenic effects in retinal models. Hyaluronan enhances stability of gold nanoparticles in different media and pHs. GNPs inhibit advanced glycated end products, cell death and neovascularization.